1987
DOI: 10.1302/0301-620x.69b1.3818718
|View full text |Cite
|
Sign up to set email alerts
|

Fat embolism and the fat embolism syndrome. A double-blind therapeutic study

Abstract: Fifty-five adults who had sustained a tibial fracture, or a femoral fracture, or both, were subjected to a double-blind randomised study to determine the efficacy of methylprednisolone in treating the fat embolism syndrome. This drug maintained arterial oxygen levels, stabilised or reduced the serum level of free fatty acids, and decreased the risk of the fat embolism syndrome in a statistically significant proportion of patients. Gurd's criteria for the diagnosis of the fat embolism syndrome were found inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 7 publications
1
136
0
10
Order By: Relevance
“…However, gas exchange deteriorates after long bone fractures with or without FE. In 16 of 28 patients with lower limb long bone fractures, the oxygen tension (P a o 2 ) was reported to be less than 7.3 kPa [5] and, similarly, in another study of patients with multiple injuries, the P a o 2 was reported to be less than 9.3 kPa in 90% of patients [8].…”
Section: Q 2001 Blackwell Science Ltdmentioning
confidence: 87%
See 3 more Smart Citations
“…However, gas exchange deteriorates after long bone fractures with or without FE. In 16 of 28 patients with lower limb long bone fractures, the oxygen tension (P a o 2 ) was reported to be less than 7.3 kPa [5] and, similarly, in another study of patients with multiple injuries, the P a o 2 was reported to be less than 9.3 kPa in 90% of patients [8].…”
Section: Q 2001 Blackwell Science Ltdmentioning
confidence: 87%
“…Gurd's criteria have been criticised for being unreliable because fat droplets can frequently be found in the blood of healthy volunteers and trauma patients without any clinical evidence of FES [4]. Lindeque suggested that Gurd's criteria may underdiagnose the syndrome and proposed the following criteria based on respiratory parameters (Table 2) [5]. Any patient with a fractured femur and/or tibia showing one or more of these criteria was judged as having FES.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was small and clinical diagnosis of FES was established using Gurd's criteria [13], which have not been proved as the gold standard clinical diagnostic criteria of FES. Although some researchers believe that Gurd's criteria may underdiagnose FES, there is in fact no gold standard diagnostic criterion to identify this condition and Gurd's criteria are still the most frequently used diagnostic criteria of FES [12,14,15,22]. Some researchers believe that a high index of suspicion and close observation for the subtle signs of FES in vulnerable patients may diagnose the syndrome accurately [12,14,24].…”
Section: Discussionmentioning
confidence: 99%